Girls Who Like Boys Who Like Boys Women and Gay Male Pornography and Erotica - Neville, Lucy (Springer International Publishing, 2018)
This book investigates what women enjoy about consuming, and in some cases producing, gay male erotic media-from slashfic, to pornographic texts, to visual pornography-and how this sits within their consumption of erotica and pornography more generally. In addition, it will examine how women's use of gay male erotic media fits in with their perceptions of gender and sexuality. By drawing on a piece of wide-scale mixed methods research that examines these motivations, an original and important volume is presented that serves to explore and contribute to this under-researched area. .